Assessment of nursing home residents in Europe: the Services and Health for Elderly in Long TERm care (SHELTER) study - Onder Graziano; Carpenter Iain; Finne-Soveri Harriet; Gindin Jacob; Frijters Dinnus; Henrard Jean; Nikolaus Thorsten; Topinkova Eva; Tosato Matteo; Liperoti Rosa; Landi Francesco; Bernabei Roberto (BMC, 2012)
Abstract Background Aims of the present study are the following: 1. to describe the rationale and methodology of the Services and Health for Elderly in Long TERm care (SHELTER) study, a project funded by the European Union, aimed at implementing the interRAI instrument for Long Term Care Facilities (interRAI LTCF) as a tool to assess and gather uniform information about nursing home (NH) residents across different health systems in European countries; 2. to present the results about the test-retest and inter-rater reliability of the interRAI LTCF instrument translated into the languages of participating countries; 3 to illustrate the characteristics of NH residents at study entry. Methods A 12 months prospective cohort study was conducted in 57 NH in 7 EU countries (Czech Republic, England, Finland, France, Germany, Italy, The Netherlands) and 1 non EU country (Israel). Weighted kappa coefficients were used to evaluate the reliability of interRAI LTCF items. Results Mean age of 4156 residents entering the study was 83.4 ± 9.4 years, 73% were female. ADL disability and cognitive impairment was observed in 81.3% and 68.0% of residents, respectively. Clinical complexity of residents was confirmed by a high prevalence of behavioral symptoms (27.5% of residents), falls (18.6%), pressure ulcers (10.4%), pain (36.0%) and urinary incontinence (73.5%). Overall, 197 of the 198 the items tested met or exceeded standard cut-offs for acceptable test-retest and inter-rater reliability after translation into the target languages. Conclusion The interRAI LTCF appears to be a reliable instrument. It enables the creation of databases that can be used to govern the provision of long-term care across different health systems in Europe, to answer relevant research and policy questions and to compare characteristics of NH residents across countries, languages and cultures.